TEST OF DIFFERENT LEVELS OF GENERAL BANKING HEALTH LISTED ON THE INDONESIAN STOCK EXCHANGE 2018-2022 USING THE RGEC METHOD - Setya Pradhana, Moch Aldi; Prajawati, Maretha Ika (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This research aims to analyze the comparative level of health of commercial banks using the RGEC method: (Risk profile, Good Cooperative Governance, Earnings and Capital). The use of the RGEC method has been determined by BI (Bank Indonesia) and has been used since 2012 and is stipulated in PBI number 13/1/PBI/2011. The objects used in this research are Islamic commercial banks with a total of 9 banks that have the largest assets and are registered on the BEI (Financial Services Authority) and have annual reports and GCG (Good Corporate Governance) reports. Research that uses quantitative methods uses comparative analysis and uses non-parametric tests. Based on the research results, show that the risk profile variable is assessed using LDR (Loan to Deposit Ratio), the GCG variable comes from PDN Net Open Exchange Position, the Earnings variable uses ROA (Return On Assets), the Capital variable is based on risk profile factors which are measured using CAR (Capital Adequacy). Ratio), Bank health variables are measured using NOM (Net Operating Margin). Variables that have ratios because this research uses ratio values as a comparison. Significant comparison results indicate that there are significant differences in each variable.